IMPROVING THE ACCOUNTING OF REVENUES AND EXPENSES - Ochilov Farxodjon Shavkatjon ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article describes the characteristics of forming financial indicators and their analytical results. Additionally, it examines the processes of applying the principles of accounting in calculating revenues and expenses, and it develops recommendations for a more effective organization of these processes. The research findings contribute to enhancing the accuracy of financial indicators, ensuring the transparency of reporting, and optimizing the decision-making process for management. These recommendations will assist in improving the financial stability and competitiveness of organizations.